2022
DOI: 10.1002/hed.27067
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of metastatic lateral lymph node ratio for recurrence in pathologically lateral lymph node‐positive papillary thyroid cancer patients with palpable lymph nodes

Abstract: Background: This study aimed to identify the predictive value of the extent of metastatic lymph nodes in the central and lateral neck compartment for recurrence in papillary thyroid cancer (PTC) patients with pathologically lateral lymph node metastasis (pN1b).Methods: This study enrolled 252 patients with pN1b from PTC.Results: During a mean follow-up of 17.6 years, 55 (21.8%) patients experienced recurrence. Patients with palpable lymph nodes were more likely to have a recurrence than those with nonpalpable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Dong et al . 19 reported that a PLR of at least 50% in the lateral neck was associated with poor RFS in PTC. In addition, Noel and Orloff 20 suggested that patients with postoperatively evaluated stimulated Tg (indicating persistent disease) had a lower LNY and a higher PLR during their initial neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al . 19 reported that a PLR of at least 50% in the lateral neck was associated with poor RFS in PTC. In addition, Noel and Orloff 20 suggested that patients with postoperatively evaluated stimulated Tg (indicating persistent disease) had a lower LNY and a higher PLR during their initial neck dissection.…”
Section: Discussionmentioning
confidence: 99%